Effect of heavy interstitials on anelastic properties of Nb-1.0 wt% Zr alloys - de Souza, Armando Cirilo [UNESP]; Grandini, Carlos Roberto [UNESP]; Florencio, Odila (Springer, 2008)
The mechanical properties of metals with bcc structure, such as niobium and its alloys, have changed significantly with the introduction of heavy interstitial elements. These interstitial elements (nitrogen, for example), present in the alloy, occupy octahedral sites and constitute an elastic dipole of tetragonal symmetry and might produce anelastic relaxation. This article presents the effect of nitrogen on the anelastic properties of Nb-1.0 wt% Zr alloys, measured by means of mechanical spectroscopy using a torsion pendulum. The results showed complex anelastic relaxation structures, which were resolved into their constituent peaks, representing each relaxation process. These processes are due to stress-induced ordering of the interstitial elements around the niobium and zirconium of the alloy.